2012
DOI: 10.1002/ca.22132
|View full text |Cite
|
Sign up to set email alerts
|

The supratrochlear foramen of the humerus in a south african dry bone sample

Abstract: The supratrochlear foramen (STF) of the humerus is the aperture that forms when the septum separating the coronoid and olecranon fossa is perforated. There are no known studies in the literature on the STF among various South African ethnic groups. The presence and shapes of the STF were established by visual observation from a sample of 538 skeletonized individuals with paired humeri (1,076) and of equal numbers between the sexes. Measurements of the transverse (TD) and vertical (VD) distance of the STF were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 13 publications
5
31
0
1
Order By: Relevance
“…Lamina perforation among males had frequently been observed on the right humerus, while among females and younger adults it was more frequent on the left humerus, resulting in more septal apertures than in older ones (all these differences insignificant). These results are in contradiction to the majority of studies, where it was more prevalent in females [2,17,29,32,33,43], and left asymmetry has commonly been observed [2,17,18,23,29,33,34,35,43]. However, there are reports of higher incidence of subtrochanter foramen among males [12,24].…”
Section: Discussionmentioning
confidence: 73%
“…Lamina perforation among males had frequently been observed on the right humerus, while among females and younger adults it was more frequent on the left humerus, resulting in more septal apertures than in older ones (all these differences insignificant). These results are in contradiction to the majority of studies, where it was more prevalent in females [2,17,29,32,33,43], and left asymmetry has commonly been observed [2,17,18,23,29,33,34,35,43]. However, there are reports of higher incidence of subtrochanter foramen among males [12,24].…”
Section: Discussionmentioning
confidence: 73%
“…Different studies have observed that the larger size of the olecranon fossa and lesser breadth of the distodorsal pillars in Neanderthals compared with H. sapiens is a classical feature of this human group (Vandermeersch and Trinkaus, 1995;Bacon, 2000;Rosas et al, 2015). There are several studies about septal perforation in the modern human population (Singhal and Rao, 2007;Ndou et al, 2013) that suggest that the larger size and septal perforation are the result of bone resorption caused by an intermittent pressure of ulna olecranon or coronoid processes on the septum of the humerus during the flexion-extension movement of the elbow, which produces a greater hyperextension of this joint. In Neanderthals, this same phenomenon could explain the larger size of the left olecranon fossa.…”
Section: Discussionmentioning
confidence: 99%
“…U nedospělých jedinců bývá zaznamenán jen velmi zřídka a jeho formování spadá ve většině případů do období rané dospělosti (Mays 2008). Většina studií zaznamenala vyšší výskyt této variety u žen (Diwan et al 2013;Benfer-McKern 1966;Ndou et al 2013;Mays 2008). Výskyt otvoru byl u většiny zkoumaných populací častější na levých pažních kostech (Erdogmus et al 2014;Patel et al 2013).…”
Section: čUta T Mořkovskýunclassified